USLŪB AL-TIKRĀR FĪ SŪRAH AL-MUAWIŻATAIN - Huda, Nur (UIN Raden Mas Said Surakarta, 2020)
This study aims to describe the repetition and its effect in the muawwiżatain surah. This research is a qualitative study using descriptive methods. Qualitative research is one of the research procedures that analyzes descriptive data in the form of observed speech or writing. Descriptive method aims to describe and analyze data about the style of repetition in muawwiżatain. Repetition is a form of repetition, both in terms of sounds, syllables, words, or sentence parts that are considered important to put pressure in accordance with the expected context. This research confirms the existence of rhetorical language in the form of repetition that is contained and spread in muawiżatain surahs giving greater influence and effect in the hearts and minds of readers. In this study, found 7 (seven) types of repetition, each of which is alliteration, rhyme, asonance, epizueksis, epistrofa, simploke, and anaphora. This research confirms that repetition as a form of language style is very different from repetition as a form of weakness of writers or authors. In addition, repetition has an important role in optimizing the repetition function which incidentally helps in emphasizing the intent and giving certain effects.